First trimester exposure to ambient gaseous air pollutants and risk of orofacial clefts: a case-control study in Changsha, China - Wen Jiang; Wanqin Xie; Bin Ni; Haiyan Zhou; Zhiyu Liu; Xingli Li (BMC, 2021)
Abstract Background A growing body of studies have investigated the association between air pollution exposure during early pregnancy and the risk of orofacial clefts, but these studies put more emphasis on particulate matter and reported inconsistent results, while research on the independent effects of gaseous air pollutants on orofacial clefts has been quite inadequate, especially in China. Methods A case-control study was conducted in Changsha, China from 2015 to 2018. A total of 446 cases and 4460 controls were included in the study. Daily concentrations of CO, NO2, SO2, O3, PM2.5 and PM10 during the first trimester of pregnancy were assigned to each subject using the nearest monitoring station method. Multivariate logistic regression models were applied to evaluate the associations of monthly average exposure to gaseous air pollutants with orofacial clefts and its subtypes before and after adjusting for particulate matter. Variance inflation factors (VIFs) were used to determine if the effects of gaseous air pollutants could be independent of particulate matter. Results Increase in CO, NO2 and SO2 significantly increased the risk of cleft lip with or without cleft palate (CL/P) in all months during the first trimester of pregnancy, with aORs ranging from 1.39 to 1.48, from 1.35 to 1.61 and from 1.22 to 1.35, respectively. The risk of cleft palate only (CPO) increased with increasing NO2 exposure levels in the first trimester of pregnancy, with aORs ranging from 1.60 to 1.66. These effects sustained and even exacerbated after adjusting for particulate matter. No significant effect of O3 was observed. Conclusions Our study suggested that maternal exposure to CO, NO2, and SO2 during the first trimester of pregnancy might contribute to the development of orofacial clefts, and the associations were potentially independent of particulate matter.